Perancangan Ulang Tata Letak Lantai Produksi Berdasarkan Metode 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) - Alya Ulfatul Jannah; Mohamad Hakam; Fitri Hardiyanti (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
A company engaged in metal casting is building a steel casting project. The layout design in the project has several problems, including the utilization of the area is not optimal, does not pay attention to the proximity relationship between facilities so that excessive movement in material handling occurs. This can affect the productivity of the company. This study aims to determine the total distance of material handling movements so that the selected alternative layout will be obtained. The selected layout can increase efficiency by 4.06% in the total distance of material handling movements. The results of the 5S evaluation using the respondent response sheet on the selected layout have a total score of seiri 4.47, seiton score 4.43, seiso score 4.50, seiketsu score 4.20 and shitsuke score 4.30. Overall, the score is 4.38, so based on the Likert scale it can be categorized as very good.